How Have the World's Poorest Fared Since the Early 1980s? - Chen, Shaohua; Ravallion, Martin (World Bank, Washington, D.C., 2013)
The authors present new estimates of the extent of the developing world's progress against poverty. By the frugal $1 a day standard, they find that there were 1.1 billion poor in 2001-almost 400 million fewer than 20 years earlier. Over the same period, the number of poor declined by more than 400 million in China, though half of this decline was in the first few years of the 1980s. The number of poor outside China rose slightly over the period. A marked bunching up of people between $1 and $2 a day has also emerged. Sub-Saharan Africa has become the region with the highest incidence of extreme poverty and the greatest depth of poverty. If these trends continue, then the aggregate $1 a day poverty rate for 1990 will be halved by 2015, though only East and South Asia will reach this goal.